2004
DOI: 10.1016/j.ccr.2004.10.015
|View full text |Cite
|
Sign up to set email alerts
|

MOZ-TIF2, but not BCR-ABL, confers properties of leukemic stem cells to committed murine hematopoietic progenitors

Abstract: To better understand the origin of leukemic stem cells, we tested the hypothesis that all leukemia oncogenes could transform committed myeloid progenitor cells lacking the capacity for self-renewal, as has recently been reported for MLL-ENL. Flow-sorted populations of common myeloid progenitors and granulocyte-monocyte progenitors were transduced with the oncogenes MOZ-TIF2 and BCR-ABL, respectively. MOZ-TIF2-transduced progenitors could be serially replated in methylcellulose cultures and continuously propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
451
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 627 publications
(482 citation statements)
references
References 41 publications
29
451
2
Order By: Relevance
“…Since these LSC -particularly in their dormant stage -may survive treatment and give rise to subsequent relapse [19,[28][29][30][31][32][33][34][35][36][37][38][39]. The latter idea is supported by a recent study showing that a higher level of putative CD34 + /CD38 --LSC is associated with a worse prognosis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Since these LSC -particularly in their dormant stage -may survive treatment and give rise to subsequent relapse [19,[28][29][30][31][32][33][34][35][36][37][38][39]. The latter idea is supported by a recent study showing that a higher level of putative CD34 + /CD38 --LSC is associated with a worse prognosis [40].…”
Section: Discussionmentioning
confidence: 99%
“…In support of the involvement of p300 and CBP, the CID of TIF2 is crucial for these activities. Unlike BCR-ABL, MOZ-TIF2 confers self-renewal properties to committed murine hematopoietic progenitors and its expression results in AML that can be serially transplanted, so MOZ-TIF2 is a unique leukemic gene product (Huntly et al, 2004). At the molecular level, MOZ-TIF2 depletes CBP from PML bodies to inhibit transcriptional activity of p53 and the retinoic acid receptor RAR (Kindle et al, 2005;Collins et al, 2006).…”
Section: Moz and Morf In Leukemia Leiomyomata And Other Malignanciesmentioning
confidence: 99%
“…Identification of the cell type from which a given type of tumor arises (that is, the cell of origin) can form a basis for understanding the tumor biology and provide important clues for the development of diagnosis and therapy. Previous data on hematological malignancies have shown that not only multipotent stem cells, but also committed progenitor cells are susceptible to malignant transformation (Cozzio et al, 2003;Huntly et al, 2004;Krivtsov et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the observation that similar histological malignancies develop when multipotent hematopoietic stem cells and committed progenitor cells are exposed to the same oncogenic stressor (Cozzio et al, 2003). Furthermore, there is evidence that the nature of oncogenic stress and the particular differentiation properties or state of the cell of origin may have critical roles in tumorigenic activity and tumor histological type (Huntly et al, 2004). Although accumulated evidence has clarified the cancer cell of origin and mechanisms of transformation in hematological malignancies, such aspects of mesenchymal tumors are largely unknown.…”
Section: Introductionmentioning
confidence: 99%